Hubungan Pengetahuan Dan Persepsi Dengan Pengambilan Keputusan Penggunaan Alat Kontrasepsi Dalam Rahim Pasca Plasenta Pada Ibu Hamil Trimester III - Wijayanti, Yuni; Arifin Senjaya, Asep; Sri Erawati, Ni Luh Putu (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2026)
Introduction Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia remain high. One effort to address this issue is increasing the use of contraception, particularly Long-Acting Reversible Contraceptives (LARC) such as the Post-Placental Intrauterine Device (IUD). However, the coverage of post-placental IUD use remains low. This study aimed to analyze the relationship between knowledge level and perception with decision-making regarding post-placental IUD use among third-trimester pregnant women. Method This study used a descriptive correlational design and was conducted in the working area of UPTD Puskesmas I Denpasar Timur from April to May 2025. The sample consisted of 38 respondents selected using purposive sampling, and data were collected through questionnaires measuring knowledge and perception. Result The results showed that 44.7% of respondents had sufficient knowledge, 31,6% had negative perceptions, and 52.6% planned to use other contraceptive methods. The Chi-Square test indicated a significant relationship between knowledge and decision-making (p = 0.004) and a highly significant relationship between perception and decision-making (p = 0.000). Conclusion It is concluded that there is a significant relationship between knowledge and perception with decision-making regarding post-placental IUD use. It is recommended that health workers intensify education and counseling for third-trimester pregnant women regarding the benefits, effectiveness, and safety of post-placental contraception.